Deconstructing Tarjih: Analisis Kritis Metode Tarjih dalam Penetapan Hukum Islam Kontemporer dan Relevansinya Terhadap Manajemen SDM Ekonomi Syariah - Wira Syuhada; Kholilurrohman; Azmi Ismail (DPPM Universitas Pelita Bangsa, 2026)
This article examines the problems that arise in the application of the tarjih method in Indonesia, particularly in addressing contemporary Islamic legal issues related to human resources management in Islamic economic institutions. Using a qualitative approach with document analysis from three major fatwa institutions: the Muhammadiyah Tarjih Council, the Nahdlatul Ulama Council (LBM NU), and the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). This study finds that there is a significant dynamic between the established adherence to traditional school methodologies and the need for contextual ijtihad. This dynamic creates a diversity of legal products (fatwas) that often overlap or even contradict each other and have implications for economic human resources, ranging from recruitment policies and compensation systems to employee development, which must operate amidst legal uncertainty.